Building Consent: Hegemony, 'Conceptions of the World' and the Role of Evangelicals in Global Politics. (26th November 2012) - Murray, Kyle; Worth, Owen
Abstract : Since Robert Cox's early interventions in the 1980s, the work of Gramsci has been openly applied to the arena of international politics, often superimposed on to the wider concepts of 'world order' and 'transnational class' formation. While this has produced a great deal of commendable scholarly work, it has equally produced a growing number of critics who have voiced concerns over the viability and feasibility of applying Gramsci's key concepts to the realm of the international. Rather than revisiting these charges, we argue that one of the main problems associated with the 'neo‐Gramscian' interpretations of international relations (IR) is that they have tended to develop an ontology of their own and have not pursued a re‐reading of Gramsci's actual work to explore a fresh opening towards applying Gramsci to the international. We argue that by re‐exploring Gramsci's understanding of 'conceptions of the world' and by re‐examining Gramsci's concept of hegemony, a greater scope can be achieved for understanding power relations within global politics. We demonstrate the potential for this by tentatively looking at the role of increasingly popular global evangelical religious groups in the fashioning of hegemonic consent across diverse parts of civil society, arguing that it is such bottom‐up studies of societal consent that are required in order for Gramscian theory and research to move beyond their current ontological applications.